Gender in Arabic Language Learning: A Social-Educational Analysis - Azzahra, Luthfi Qolbi; Saariah, Saariah; Dahlia, Iis; Setiyawan, Agung (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This research aimed to determine gender relationships in Arabic language learning in social-educational studies. The method used in this research employed a library approach with the data source being actual and factual literacy, and Mels and Heberman data analysis was utilized using interactive techniques. The results of this research showed that gender was not a true social construct or form, was not innate from birth, and could not also be said to be God's nature or provision because gender was related to the process of believing how men and women should act and behave in accordance with structured values, social and cultural provisions in the place where they were located. Learning Arabic could not be separated from linguistics and was included in the subcategory of grammar, especially in understanding the placement of mudzakkar and muannast. In the structure of the Arabic language, masculinity was the fundamental that was subjected, while femininity was the branch that had no ability as a subject